Perbedaan Kadar Quercetin pada Propolis Isolat Gunung Lawu antara yang Diekstrak dengan Etanol dan Propylene Glycol - Pristiawan Navy Endraputra; Diding Heri Prasetyo; . Sarsono (Nexus Biomedika, 2013)
Background: Propolis contains quercetin, a substance from flavonoid group which is usually found as its glycoside form and its polarity changes to polar character. More polar of the solvent used, the greater flavonoid compound obtained. Consequently, it leads to different amount of quercetin gotten by different solvents on propolis extraction method. Method: This research used the post test only group design. Aluminium chloride colorimetric assay was applied to determine the amount of quercetin obtained from both ethanolic and propylene glycol extracting procedures. The data were statistically analyzed by independent t-test method. The propolis was collected from Kerjo, Karanganyar. Result: Total dissolved quercetin in ethanolic extract and propylene glycol extract were 63.38 13.14 g/mL and 45.69 8.70 g/mL, each, p < 0.05. Conclusion: This research significantly showed that the quercetin level of propolis extracted with ethanol higher than the one extracted with propylene glycol. Keywords: Aluminium Chloride, Propolis, Quercetin